3D printing of poly(vinylidene fluoride-trifluoroethylene): a poling-free technique to manufacture flexible and transparent piezoelectric generators. (7th February 2019) - Shepelin, Nick A.; Lussini, Vanessa C.; Fox, Phillip J.; Dicinoski, Greg W.; Glushenkov, Alexey M.; Shapter, Joseph G.; Ellis, Amanda V.
Abstract: Abstract : Flexible piezoelectric generators (PEGs) present a unique opportunity for renewable and sustainable energy harvesting. Here, we present a low-temperature and low-energy deposition method using solvent evaporation-assisted three-dimensional printing to deposit electroactive poly(vinylidene fluoride) (PVDF)-trifluoroethylene (TrFE) up to 19 structured layers. Visible-wavelength transmittance was above 92%, while ATR-FTIR spectroscopy showed little change in the electroactive phase fraction between layer depositions. Electroactivity from the fabricated PVDF-TrFE PEGs showed that a single structured layer gave the greatest output at 289.3 mV peak-to-peak voltage. This was proposed to be due to shear-induced polarization affording the alignment of the fluoropolymer dipoles without an electric field or high temperature.